PELATIHAN TARI RANTAK DALAM KEGIATAN EKSTRAKURIKULER DI SMK NEGERI 9 PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of Rantak Dance training in extracurricular activities at SMK Negeri 9 Padang. This research used a qualitative method with a descriptive approach. The object of the study was the implementation of Rantak Dance training involving 16 students participating in dance extracurricular activities. Data were collected through observation, documentation, and literature study. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing. The results showed that the training was implemented through several stages, namely preparing and organizing training groups, identifying learning needs and training objectives, designing training programs, demonstration methods, practice activities, movement observation, evaluation, repetitive exercises, and performance simulation. The training process was carried out gradually from movement variation 1 to movement variation 13. The implementation of the training improved students’ mastery of movement, rhythm, expression, energy control, ability to follow musical accompaniment, and group cohesiveness. Therefore, the implementation of Rantak Dance training in extracurricular activities at SMK Negeri 9 Padang was carried out successfully and contributed to improving students’ dance abilities.